Soil constraints for arbuscular mycorrhizal fungi spore community in degraded sites of rupestrian grassland: Implications for restoration - Coutinho, Etiene Silva; Barbosa, Milton; Beiroz, Wallace; Mescolotti, Denise L.C.; Bonfim, Joice Andrade; Louro Berbara, Ricardo Luís; Fernandes, Geraldo W (European journal of soil biology, 2019)
The arbuscular mycorrhizal fungi (AMF) are important organisms with enormous potential for use in ecological restoration due to their positive association to seedlings. We evaluated the effects of soil degradation on a species-rich AMF community that could hinder the restoration of rupestrian grassland sites whose soil had been removed. Soil samples were taken from reference and degraded sites. We assessed the density, species richness, and composition of AMF, as well as soil macronutrients, metals, and texture. We found lower AMF density and richness in degraded than in reference sites. AMF community seemed to be negatively affected by a low level of potassium (K) and a higher concentration of heavy metals and clay in degraded sites. Besides the shifts in AMF composition associated mainly with K concentration, we found that the lack of this nutrient in degraded sites was also related to a significant reduction in density of AMF species, which are thought to play important roles in plant development and, therefore, in ecological restoration. Thus, we emphasize that efforts to restore degraded areas of rupestrian grassland should contemplate the reestablishment of soil physical and chemical properties, such as a lower clay concentration, and levels of nutrients that are key for AMF colonization. In addition, we suggest the further development of protocols for inoculation of seedlings and soil with AMF species to improve the success of replantation. •Soil removal severely affects the AMF community in rupestrian grassland.•Degradation of AMF communities can be correlated with drop of available K concentration.•Restoration of rupestrian grassland should start with rectification of soil conditions.•Besides, we suggest that seedlings should be inoculated with AMF before replantation.